Geology of the Inner Lesser Himalaya between Kusma and Syangja in Western Nepal - Dhital, Megh Raj; Thapa, Prem Bahadur; Ando, Hisao (Bulletin of the Department of Geology, 2008)
The inner Lesser Himalayan rocks constituting the Ksuma-Syangja area in western Nepal are separated into the Lower Nawakot Group, Upper Nawakot Group, Sirkot Group, and Tansen Group, respectively from bottom to top. The Lower Nawakot Group is further divided into the Kuncha Formation (alternating bands of grey-green gritty phyllite and metasandstone), Naudanda Quartzite (very thick-bedded, pale yellow to white quartzite), Nayagaun Formation (grey-green phyllite and slate), Norpul Fromation (red-purple, grey, and grey-green slate and quartzite), and Dhading Dolomite (grey dolomite with columnar stromatolites), respectively from bottom to top. The Dhading Dolomite transitionally passes into the overlying Benighat Slates (interlaminates black slate with sporadic carbonate bands) of the Upper Nawakot Group. The Sirkot Group succeeds the Benighat Slates and is divided into the Sorek Fromation (grey-green and red-purple slate and orthoquartzite together with the Ripa Member of grey dolomite containing columnar and dome-shaped stromatolites) and the overlying Dhanpure Limestone(parallel-laminated grey limestone and shale). The Tansen Group disconformably overlies the above rocks, and is represented by the Sisne Fromation(grey diamictite), Amile Fromation (grey to brown orthoquartzite interbedded with brown and red-purple shale), and Dumri Formation (red-purple shale and grey-green sandstone), respectively in an ascending order. Based on lithostratigraphic similarities and occurrence of stromatolites, it is inferred that the Lower Nawakot Group is equivalent to the Damtha Group and the Deoban Formation whereas the Benighat Slates are comparable with teh Mandhali Fromation of the Kumao Himalaya, India.Similarly, the Sirkot group is equivalent to the kali Gandaki supergroup and Gwar group of the outer lesser himalaya of Nepal. The Sirkot group is also comparable with the Nagthat, Blaini, and Krol Formations of the Krol Belt in the Kumaon lesser Himalayan of India. The Main Central Thrust (MCT) covered the entire inner lesser Himalaya in the past and the Kusma -Syangja area was part of a complex duplex system .The MCT acted as a roof thrust and minimum displacement along it is estimated at 80 km. The sedimentary and low-grade metamorphic rocks of inner lesser Himalaya were sandwiched between the MCT and a sole thrust lying at an inferred depth of 6-7 km. Consequently, they underwent intense deformation resulting in the development of foreland- as well as hinterland -vergent imbricate faults. The southward propagation of the duplex was responsible for the development of south-vergent mesoscopic as well as small-scale folds near the anatomosing leading edge branch lines. A triangle zone was formed in the area bounded by two thrusts with opposite vergence and same basal detachment. Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 9, 2002, pp. 1-60